Titania Nanosheet Generates Peroxynitrite-Dependent S-Nitrosylation and Enhances p53 Function in Lung Cancer Cells - Rapeepun Soonnarong; Sucharat Tungsukruthai; Bodee Nutho; Thanyada Rungrotmongkol; Chanida Vinayanuwattikun; Tosapol Maluangnont; Pithi Chanvorachote (Pharmaceutics, 2021)
Metal nanomaterials can enhance the efficacy of current cancer therapies. Here, we show that Ti0.8O2 nanosheets cause cytotoxicity in several lung cancer cells but not in normal cells. The nanosheet-treated cells showed certain apoptosis characteristics. Protein analysis further indicated the activation of the p53-dependent death mechanism. Transmission electron microscopy (TEM) and scanning electron microscopy (SEM) analyses revealed the cellular uptake of the nanosheets and the induction of cell morphological change. The nanosheets also exhibited a substantial apoptosis effect on drug-resistant metastatic primary lung cancer cells, and it was found that the potency of the nanosheets was dramatically higher than standard drugs. Ti0.8O2 nanosheets induce apoptosis through a molecular mechanism involving peroxynitrite (ONOO−) generation. As peroxynitrite is known to be a potent inducer of S-nitrosylation, we further found that the nanosheets mediated the S-nitrosylation of p53 at C182, resulting in higher protein-protein complex stability, and this was likely to induce the surrounding residues, located in the interface region, to bind more strongly to each other. Molecular dynamics analysis revealed that S-nitrosylation stabilized the p53 dimer with a ΔGbindresidue of <−1.5 kcal/mol. These results provide novel insight on the apoptosis induction effect of the nanosheets via a molecular mechanism involving S-nitrosylation of the p53 protein, emphasizing the mechanism of action of nanomaterials for cancer therapy.
Keywords: Nanoplatforms for cancer theranostics; Advanced Nanomaterials in Catalysis; Immune cells in cancer